2018
DOI: 10.1093/cvr/cvy163
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-specific deficiency of HSPB1 worsens cardiac dysfunction by activating NFκB-mediated leucocyte recruitment after myocardial infarction

Abstract: These data suggest that HSPB1 acts as a negative regulator of NFκB-mediated leukocyte recruitment and the subsequent inflammation in cardiomyocytes. Cardiomyocyte HSPB1 is required for wound healing after MI and could be a target for myocardial repair in MI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 39 publications
1
50
0
Order By: Relevance
“…Specifically, by their expression level, HSPB6 (also refers to HSP20) was decreased by 44%, HSPB2 was decreased by 31%, HSPB5 (also refers to CRYAB) was decreased by 58%, and HSPB1 (also refers to HSP27) was increased by 39%. These 4 HSPBs are all recognized to have cardioprotective effects in the heart against stress‐induced injuries including MI and cardiac hypertrophy, mainly through modulating apoptotic process (Mitra et al, 2013; Wang et al, 2019). Particularly, studies have shown that HSPB1 is an essential regulator on alleviating inflammation in myocardial repair after MI and maintaining cardiac function against atrial fibrillation (Brundel et al, 2006; Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, by their expression level, HSPB6 (also refers to HSP20) was decreased by 44%, HSPB2 was decreased by 31%, HSPB5 (also refers to CRYAB) was decreased by 58%, and HSPB1 (also refers to HSP27) was increased by 39%. These 4 HSPBs are all recognized to have cardioprotective effects in the heart against stress‐induced injuries including MI and cardiac hypertrophy, mainly through modulating apoptotic process (Mitra et al, 2013; Wang et al, 2019). Particularly, studies have shown that HSPB1 is an essential regulator on alleviating inflammation in myocardial repair after MI and maintaining cardiac function against atrial fibrillation (Brundel et al, 2006; Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These 4 HSPBs are all recognized to have cardioprotective effects in the heart against stress‐induced injuries including MI and cardiac hypertrophy, mainly through modulating apoptotic process (Mitra et al, 2013; Wang et al, 2019). Particularly, studies have shown that HSPB1 is an essential regulator on alleviating inflammation in myocardial repair after MI and maintaining cardiac function against atrial fibrillation (Brundel et al, 2006; Wang et al, 2019). Taken all together, EtOH can suppress as well as evoke the defense system against oxidative stress‐related apoptosis in hiPSC‐CMs.…”
Section: Discussionmentioning
confidence: 99%
“…With the extension of the inflammatory phase in the diabetic wound-healing process, inflammatory cells were generally activated, thus delaying the switch from inflammatory phase to proliferative phase [4]. A large amount of inflammatory mediators, such as tumor necrosis factor (TNF)-a and interleukin (IL)-6, secreted by cells were released into the wound site and subsequently prevented the cell proliferation and migration required for diabetic wound healing [5]. Furthermore, over-activation of inflammation increased matrix metalloproteinase (MMP)-9 expression [6,7], which resulted in rapid degradation of native collagen, fibronectin, and elastin, thus delaying the diabetic wound-healing process [8].…”
Section: Introductionmentioning
confidence: 99%
“…IGF2 may be relevant to the regeneration of the mammalian heart after injury [55], of which expression is induced to increase by hypoxia in rat hearts [56]. An experiment suggested that HSPB1 acts a role that reduced in ammation and healed wound after myocardial infarction(MI), expected to be a target for myocardial repair in MI patients [57]. CRP, which is one of the in ammatory biomarkers, is considered to be an indicator for evaluating severity and prognosis of CHD, as lipoproteins in ammation is considered signi cant in the pathogenesis of CHD [58].…”
Section: Discussionmentioning
confidence: 99%